Myocardial involvement in mumps infection [Çocuklarda kabakulak enfeksiyonuna baǧli kalp tutulumunun ekokardiyografi ve troponin-T düzeyleri ile araştirilmasi] - (:unkn) unknown (Kare Publishing, 2006)
Aim: Myocarditis is a rare, potentially lethal complication of mumps. Definitive diagnosis of myocarditis is possible by histologic examination of the myocardium. However, myocardial biopsy is an invasive method and is not performed in most of the cases. Other non-invazive methods for the diagnosis of myocardial involvement is searched for. Elevated levels of cardiac troponin-T is found to be helpful in the early detection of cardiac complications in various disease states in adult and pediatric patients. In this study, cardiac involvement in mups is searched for using echocardiography and serum troponin levels. Material and Method Our study included 66 patients ( 20 girls, 46 boys) with mumps; between the ages of 1 to 14 years. Serum troponin-T levels were measured in all patients in addition to physical cardiac examination, electrocardiography and echocardiographic examination. Results: Left ventricular ejection fraction was below the normal range in three patients, two patients had sinus bradicardia, mild mitral regurgitaion was found in four patients, and mild aortic regurgitation was found in one patient. One of the patients with decreased ejection fraction had mitral regurgitation and one other had sinus bradycardia. The number of the patients with cardiac involvement was eigth (12%). These cardiac findings were resolved during the convalescence period of the disease and the ejection fraction was found to be normal. Cardiac involvement was significantly more prevelant in patients with meningitis compared to the patients without meningitis (p<0.001). Cardiac troponin-T levels were below the measurable level (<0.01) in all patients and there was no difference between the patients with meningitis and without meningitis. Conclusions: The heart is affected during Mumps infection. However this involvement does not cause increased levels of troponin-T.
Keywords: Echocardiography; Mumps; Myocarditis; Troponin-T